Hydrothermal Synthesis of Modified Hydrophobic Zn–Al-Layered Double Hydroxides Using Structure-Directing Agents and Their Enhanced Adsorption Capacity for -Nitrophenol - Yayue Sun; Jiabin Zhou; Ya Cheng; Jiaguo Yu; Weiquan Cai (Adsorption Science & Technology)
Hollow microspheres of hierarchical ZnAl-layered double hydroxides (LDHs) were synthesized by a simple hydrothermal method using hexamethylenetetramine as precipitating agent, sodium dodecyl benzene sulphonate (SDBS) as surfactant and sodium tartrate, sodium citrate and sodium salicylate (SS) as structure-directing agents, respectively. Characterization results of the microspheres synthesized indicate that the modified ZnAl–LDHs formed a variety of morphologies, surface areas and pore volumes. The hierarchical porous ZnAl/SDBS–LDH prepared using SS possesses the highest surface area (128.9 m 2 /g) and the greatest pore volume (0.37 cm 3 /g). A possible formation mechanism of the special three-dimensional nanostructures from the primary LDH nanosheet building units is proposed on the basis of the interaction between SS molecules and LDH crystals. The size of the channel height is approximately equal to the diameter of the intercalated anion SDBS, indicating that SDBS is in a vertical single-layer arrangement. using p -nitrophenol as model pollutant, the effects of initial concentration of p -nitrophenol and contact time on the adsorption of p -nitrophenol using various ZnAl–LDHs were investigated by performing a series of experiments. Results of these experiments indicate that the microsphere hydrophobic ZnAl/SDBS–LDH modified using SS has a maximum p -nitrophenol adsorption capacity of 101.6 mg/g.